Investigating the Relationship between Positive and Negative Affect Experiences and Resilience and Tolerance of Ambiguity among Patients with HIV - Karim Babaei; Sobhan Gholmohammadzade; asghar Mohammadpur asl; Marzie Sattari (Fasa University of Medical Sciences, 2021)
Background & Objective: Patients with HIV experience considerable negative affects, which may jeopardize their physical, mental, and social health. On the other hand, resilience and ambiguity tolerance in challenging situations may increase the psychological health of high-risk individuals, specifically HIV patients who are exposed to high levels of risk and stress. Hence, the present study aimed to investigate the relationship between positive and negative affect experiences and resilience and ambiguity tolerance among patients with HIV in 2019. Materials & Methods:  This study used a descriptive-correlational design. Out of the HIV patients recorded in Hematological and Oncological Research Center, Tabriz University of Medical Sciences, 95 cases were selected via simple random sampling method and, then, they were included in the study. Afterwards, data collection was performed using resilience, ambiguity tolerance, and PANAS (positive and negative affect schedule) questionnaires. Subsequently, multiple regression analysis was used to analyze the collected data. Results: There was a significantly negative relationship between the negative affect experiences and ambiguity tolerance and resilience. Besides, the positive affect experiences were shown to have a significantly positive relationship with resilience and ambiguity tolerance. In addition, results of the regression demonstrated that the resilience and ambiguity tolerance variables could appropriately predict the positive and negative affect experiences. Conclusions: Considering the difficult conditions of the patients with HIV as well as their great number of problems, it might be possible to reduce the experiences of negative affect and, as a result, prevent the consequent outcomes of negative affect by increasing ambiguity tolerance and resilience.